Survey of the Relationship between Indoor Physical Air Quality (PM1, PM2.5, PM10) and Symptoms of Sick Building Syndrome in Employees at the Plaju Primary Health Care and Alang-Alang Lebar Primary Health Care Palembang 2024 - Dian Widia Lestari; Agita Diora Fitri; Emma Novita (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Sick Building Syndrome (SBS) is a collection of symptoms that workers in office buildings experience that are related to the air quality and amount of time they spend there. One of the dangerous indoor air pollutants is particulate matter (PM). This study aims to determine the relationship between physical air quality (PM1, PM2.5, PM10) in the room and symptoms of Sick Building Syndrome. This study is an observational analytic study with a cross-sectional design. This study used primary data in the form of measurement of physical air quality indicators and distribution of questionnaires regarding SBS at Plaju Primary Health Care and Alang-Alang Lebar Primary Health Care Palembang. This study is only a survey. The research sample consisted of 74 respondents who satisfied the inclusion and exclusion criteria. The results of the univariate analysis showed that 48.6% of respondents experienced SBS and 51.4% did not experience SBS. 20.3% of respondents in this study were ≥45 years old, 93.2% of respondents were female, and 75.7% of respondents had worked for >3 years. Two rooms in Alang-Alang Lebar Primary Health Care did not meet the applicable particulate matter standards, namely the registration room (PM1 50 μg/m3, PM2.5 80 μg/m3, and PM10 108 μg/m3) and the elderly general clinic (PM1 33 μg/m3 and PM2.5 49 μg/m3). The highest prevalence of SBS symptoms were red, itchy, dry, or watery eyes (75%) and dizziness or headache (71.4%). Age (p = 0.907), gender (p = 0.358), tenure (p = 0.077), PM1 (p = 0.873), PM2.5 (p = 0, 873), and PM10 (p = 0.431) had no significant link with the symptoms of Sick Building Syndrome at Plaju Primary Health Care and Alang-Alang Lebar Primary Health Care Palembang 2024.